2000
DOI: 10.1001/archneur.57.9.1273
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caspase 1 in Neurologic Disease

Abstract: n recent years substantial advances have taken place in understanding the mechanistic pathways mediating neuronal cell death in a variety of neurologic diseases. Since the central nervous system (CNS) has little, if any, power of functional neuronal regeneration, prevention of neuronal cell death is an important target of modern neurotherapeutics. A detailed understanding of the mechanisms mediating neuronal cell death is required to effectively slow the progression of neurologic diseases featuring apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Previous results suggesting that IL-1β does not affect ALS pathogenesis in G37R transgenic ALS mice might be due to the different aggregation and inflammatory properties of the SOD1 mutation (G93A vs. G37R) or to the different mouse strains used (congenic C57BL/6 vs. mixed background B10RIII × C57BL/6) (17). In our experiments, IL-1β deficiency slowed disease progression but did not affect disease onset, arguing for a non-cell-autonomous, microglia-mediated acceleration of neurodegeneration (25). IL-1 is a pleiotropic cytokine involved in the induction of inflammatory and neurotoxic molecules such as COX2, inducible NOS, NO, or IL-6, which are implicated in ALS (4,16,18,26).…”
Section: Discussionmentioning
confidence: 58%
“…Previous results suggesting that IL-1β does not affect ALS pathogenesis in G37R transgenic ALS mice might be due to the different aggregation and inflammatory properties of the SOD1 mutation (G93A vs. G37R) or to the different mouse strains used (congenic C57BL/6 vs. mixed background B10RIII × C57BL/6) (17). In our experiments, IL-1β deficiency slowed disease progression but did not affect disease onset, arguing for a non-cell-autonomous, microglia-mediated acceleration of neurodegeneration (25). IL-1 is a pleiotropic cytokine involved in the induction of inflammatory and neurotoxic molecules such as COX2, inducible NOS, NO, or IL-6, which are implicated in ALS (4,16,18,26).…”
Section: Discussionmentioning
confidence: 58%
“…5 Zhu et al, 20 show a 2.5-fold increase of pro-Csp-1 in AD medial temporal tissues compared to controls and Csp-1 mRNA is increased in AD. 21 The most recognized function of Csp-1 is the conversion of pro-interleukin-1b (IL-1b) into mature IL-1b thereby eliciting an inflammatory response (reviewed by Friedlander 22 ). IL-1b is increased in AD but mostly associated with microglial activation suggesting a role for Csp-1 in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have shown that activation of cas-1 is involved in the induction of fibroblast apoptosis, and cas-1 activation also seemed to be related to apoptosis in several neurodegenerative diseases and subsequent ischemic events (41,42). Cas-1 has also been shown to activate cas-3 as well as cas-6 (43).…”
Section: Discussionmentioning
confidence: 99%